2023
DOI: 10.3390/cells12081125
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies with Glioblastoma Brain Organoid Co-Cultures Show Efficient 5-ALA Photodynamic Therapy

Abstract: Background: The high recurrence of glioblastoma (GB) that occurs adjacent to the resection cavity within two years of diagnosis urges an improvement of therapies oriented to GB local control. Photodynamic therapy (PDT) has been proposed to cleanse infiltrating tumor cells from parenchyma to ameliorate short long-term progression-free survival. We examined 5-aminolevulinic acid (5-ALA)-mediated PDT effects as therapeutical treatment and determined optimal conditions for PDT efficacy without causing phototoxic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recent preclinical studies have also demonstrated the effectiveness of 5-ALA in treating glioblastoma within brain organoids, inducing cancer cell death while sparing healthy cells [130]. While this study focused on exploring the efficacy of 5-ALA to treat glioblastoma, their findings on the selective effectiveness in brain organoids provide a foundation (Figure 4).…”
Section: Pdt Applications In 3d Cancer Modelsmentioning
confidence: 99%
“…Recent preclinical studies have also demonstrated the effectiveness of 5-ALA in treating glioblastoma within brain organoids, inducing cancer cell death while sparing healthy cells [130]. While this study focused on exploring the efficacy of 5-ALA to treat glioblastoma, their findings on the selective effectiveness in brain organoids provide a foundation (Figure 4).…”
Section: Pdt Applications In 3d Cancer Modelsmentioning
confidence: 99%
“…This finding supports the role of organoids as a reliable tool in reproducing the biology of original lesions, a finding that will be crucial for the future pipeline of therapeutic testing in GBM. For instance, Pedrosa and colleagues, who utilized a GBM organoid to test for the efficacy of photodynamic therapy with 5-aminolevulenic acid (5-ALA), showed that this model simulated 5-ALA uptake, protoporphyrin IX emission, and consequent GBM cell apoptosis in a dose-dependent manner [176]. In another study, Morelli et al utilized GBOs for metabolic imaging of the tumor's response to TMZ [177].…”
Section: Gbm-brain Organotypic Models (Gboms)mentioning
confidence: 99%
“…Thus, 5-ALA-based PDT can be a potential therapeutic strategy for the treatment of different tumors. In preclinical studies the anti-tumor efficacy of 5-ALA-mediated PDT has been observed in different cancer types such as skin cancer [ 30 ], esophageal cancer [ 31 ], colon cancer [ 28 ], human glioma [ 32 ], breast cancer [ 33 ], bladder cancer [ 34 ], and hepatocellular carcinoma [ 35 ].…”
Section: Introductionmentioning
confidence: 99%